Morphohistology and Biometric Characteristics of Cecal Tonsils of Sonali Chicken at Post-Hatching Ages - Ayman, Ummay; Jahid, Md. A; Alam, Md. R; Das, Shonkor K (The Iraqi Journal of Veterinary Medicine, 2021)
Knowledge of basic structures is prerequisite for acquiring an in-depth idea about the physiology and immunology of the lymphoid system. The study evaluates the age related histomorphometry of cecal tonsil of Sonali chicken at different postnatal stages in Bangladesh as literatures regarding this are very scarce. The investigation was carried out on 25 healthy Sonali chickens representing different stage of postnatal life: days 1, 14, 28, 42, and 56 (n=5). After ethically sacrifice (cervical subluxation method), cecal tonsil was collected and subjected for both gross and histological studies. Haematoxylin and Eosin stain was done for microscopic study. Morphologically, cecal tonsils were located bilaterally at the junction of small and large intestine. It had tubular structure and yellowish white in color. All gross parameters (weight, length, and width) found to be increased significantly (P<0.05) throughout the whole study period. Weight was measured 0.022±0.001 g at day 1 and noticed 0.181±0.016 g at the end of study tenure. The microscopic observations revealed that at day 28 encapsulated lymphatic nodules was present along with the diffuse lymphocytes at the lamina propria and submucosa layer, which was absent at the previous study groups. At day 1, only small infiltration of lymphocytes was identified and at day 14, lymphocytes were aggregating to form lymphatic nodules. After that, age related development was noticed in histological features. The findings would be a milestone to give an idea about the gut health and immune status of Sonali chicken and provide a basis for further immunization research.